Low-velocity impact response of sandwich beams with a metal foam core: Experimental and theoretical investigations. (August 2019) - Xiang, Chunping; Qin, Qinghua; Wang, Mingshi; Yu, Xuehui; Chen, Shangjun; Zhang, Wei; Xia, Yuanming; Zhang, Jianxun; Zhao, Jianping; Wang, Tiejun
Highlights: The dynamic response of fully clamped sandwich beams under low-velocity impact was investigated experimentally and theoretically including the initial failure and final fracture, and the failure mechanism map was constructed to characterize the initial failure mechanism. A fracture criterion of the maximum allowed deflection was proposed to predict the final fracture. Effects of loading location, geometries, and material properties were considered for both initial failure and final fracture. Abstract: Dynamic response of fully clamped sandwich beams with a metal foam core under low-velocity impact is investigated experimentally and theoretically. Failure modes of metal sandwich beams are identified and competing initial failure mechanism map depending on the geometries and material properties is constructed to characterize the initial failure mechanism. A fracture criterion of the maximum allowed deflection is proposed based on the maximum tensile strain of face sheets to evaluate the fracture-resistance of sandwich beams. Effects of loading location, geometries, and material properties are also considered for both initial failure and final fracture. Good agreement is achieved between the experimental results and theoretical predictions. It is shown that the loading location, geometries, and material properties have significant effects on low-velocity impact response of sandwich beams.